Effects of dietary melanoidins on digestive physiology, nutrient digestibility and plasmatic antioxidant capacity of the rainbow trout Oncorhynchus mykiss - Serrano, Xavier (2018)
Melanoidins are complex molecules usually found within dietary matrixes suffering heating steps during the production process. These compounds are known to exert a number of negative effects on the digestibility of nutrients and digestive enzymes in mammals, but also determines an increase in the antioxidant capacity of the diet with potential effects for animal health. In the present work, digestive and nutritional consequences of the ingestion of glucose-glycine melanoidins were tested in juvenile rainbow trout (Oncorhynchus mykiss), which was fed two non-heated, pelletized diets: a control diet without melanoidins and an alternative diet containing 1.2% of glucose-glycine melanoidins. The results pointed to a small effect on gut pH in interaction with digestion time, and a lack of effect on gastric evacuation and digestive proteases. In addition, melanoidins were associated with a small increase in the digestibility of the diet dry matter, leaving unchanged nitrogen and phosphorus digestibility. On the other hand, melanoidins determined a complex increase in the postprandial antioxidant capacity of blood plasma, particularly apparent in the antioxidant components above 3 kDa.